Awareness and attitude of junior doctors towards BSG guidlines. (13th March 2011) - Ahmed, I; Zaidee, A; Mitchell, C
Abstract : Introduction: Clinical guidelines are intended to improve quality of care and standardise the management of well-defined clinical situations. This also enables us to set standards against which clinical practice can be assessed. Clinical guidelines have proliferated but less effort is expended over their implementation. Junior doctors deal with a wide spectrum of clinical scenario and are exposed to these guidelines. Whether this is beneficial will depend upon knowledge of their existence, usage and perceived usefulness as quality assessment tools. This study assessed junior doctors' awareness and compliance with the BSG guidelines for the management of ascites due to liver cirrhosis in a local NHS trust. Methods: A survey was sent to 75 junior doctors (20 SpR and 55 SHO) during 2007–2008 who undertook therapeutic paracentesis for liver cirrhosis. This questionnaire assessed awareness and confidence in the BSG guidelines. To assess compliance objectively, case notes of patients admitted with ascites and underwent therapeutic paracentesis over the same period were studied. The documentation of the procedure was analysed against BSG guidelines. Information was also collected from hospital electronic resources for laboratory results. The parameters assessed were consent, technique, analysis of ascitic fluid, use of albumen, drain removal and diuretics use in accordance with BSG guidelines. Results: Out of 75 doctors who were approached, 70 (93%) returned the questionnaire. All respondents perceived guidelines as effective educational tools and to improve quality of care. 88% have carried out the procedure in the last 2 years but only 55% were aware of the BSG guidelines. Out of these, only 68% claimed being compliant. Respondents had greater awareness and confidence in clinical guidelines endorsed by their hospital, but less in those by BSG. The most preferred methods for adoption were local availability, e-learning modules and education. From the case note study, a total of 50 procedures were recorded. Documentation of the procedure was available in 94% of cases. Compliance with BSG guidelines (>80%) was achieved in only 40 % of the cases and 60% were only partially compliant. Analysis of ascitic fluid, use of albumen, and drain removal were poorly compliant areas. Conclusion: This survey suggests that, although junior physicians felt that guidelines are valuable educational tools, awareness of their existence was poor as was compliance with the set standards. If clinical guidelines are to improve quality in clinical practice, they must be more effectively disseminated and implemented. To broaden junior physicians' adoption of guidelines, clinical governance must be strengthened and supported by regular and fully resourced audit. Such actions must have the active support of NHS trusts.